Implementasi Kebijakan Program Kartu Indonesia Pintar Dalam Meningkatkan Kualitas Pendidikan (Studi Pada Dinas Pendidikan Kabupaten Konawe) - Milyan, Milyan (Universitas Syiah Kuala, 2023)
The purpose of this study is to determine the Implementation of Smart Indonesia Card Policy in improving the quality of education at the Konawe District Education Office. The research subjects in this study were informants representing the Konawe District Education Office who took care of the Smart Indonesia Card and the school. This research instrument uses observation guidelines, interviews, and documentation reviews. The results showed that financial assistance through the Smart Indonesia Card (KIP) was used with the aim of easing the burden of costs that were too heavy for parents who came from lower economic status. The Konawe District Education Office always conducts evaluations to monitor the KIP program so that it remains effective and targeted. In addition, the school always monitors the allocation of KIP funds received by parents so that the funds received can really be used for their children's school needs..